Effect of self-management of stroke patients on rehabilitation based on patient-reported outcome - Sun, Yongsheng; Liu, Chengjiang; Zhang, Nianping; Yang, Debing; Ma, Jun; Ma, Cungen; Zhang, Xi (Frontiers in Neuroscience, 2022)
Objective: Investigate the effect of self-management behavior on rehabilitation of stroke patients, as an attempt to lay a theoretical basis for the use of PRO for evaluating the rehabilitation of stroke patients. Methods: 396 patients hospitalized in the Department of Neurology of 4 tertiary general hospitals in Datong from August 1, 2018 to March 31, 2020 were included in accordance with the inclusion and exclusion criteria. The included patients randomly fell into a self-management intervention group and a control group. The clinical pathway intervention was only performed for the patients of the control group in the Department of Neurology. Besides the stroke clinical pathway intervention, the three-month self-management intervention was performed for stroke patients of the intervention group. The self-management status and rehabilitation effects of the patients were evaluated in 24h and 3 months after enrollment, respectively. Statistical description and analysis were conducted using SPSS20.0 statistical software. Results: The total scores of self-management behaviors of the investigated subjects had statistical significance in different ages, occupations, educational levels, income levels, exercise intervention, past medical history, BMI, as well as marital status (P< 0.01). In this study, no statistical difference was found in different genders and medical insurance status (P>0.05). The total scores of self-management behaviors and the scores of the respective dimension were found to be positively correlated with the health education, exercise intervention, functional training, psychological intervention, food intake, living habits, and functional training of stroke patients at the recovery stage. Educational level and marital status were found to be positively correlated with the rehabilitation effect of patients. The PRO questionnaire for stroke scored higher in married patients and patients with high educational levels, and there were statistically significant differences (P<0.01). Family history was negatively correlated with the rehabilitation effect of patients. Exercise intervention and functional training were found to be positively correlated with the rehabilitation effects of patients. Conclusion: Self-management interventions could effectively increase the health education level of stroke patients, strengthen their self-confidence in disease self-management, facilitate the establishment of effective self-management behavior of patients, and improve the quality of life and subjective well-being of patients.